Serial Verb Constructions (SVCs) in Nzema: A Descriptive Analysis - John Nyame; Cecilia Tomekyin (Journal of Communication and Cultural Trends, 2022)
This paper discusses the serial verb constructions (SVCs) in Nzema, a Southern Bia (Kwa) language. It draws on some of the characteristics and properties surveyed in the literature, such as subject/object sharing, tense, aspect, and negation. Moreover, it also discusses the types and functions of SVCs in Nzema and analyses the notions of tense, aspect, and polarity, as well as how they are marked in Nzema SVCs. Most of the data used in the analysis was taken from the daily conversations of native speakers. Four native speakers of Nzema acted as respondents in this study. It shows that Nzema SVCs are of the types explored in the literature as clause chaining, integrated, and “concordial”. Serial verb patterns are used to add the argument, such as an instrument or a beneficiary. Future markers appear before the verbs, while past markers occur after the verbs. In the same vein, progressive aspect markers occur before the verbs. Moreover, tense and aspect marking is repeated on all the verbs in the series. Regarding argument sharing, the object is shared only when the verbs in the series are transitive.